Estimating the economic burden of osteoporotic fractures in a multinational study: a real-world data perspective - Moayyeri, A.; Warden, J.; Han, S.; Suh, H.S.; Pinedo-Villanueva, R.; Harvey, N.C.; Curtis, J.R.; Silverman, S.; Multani, J.K.; Yeh, E.J. (Osteoporosis international, 2023)
Summary Fracture-related costs vary by country. A standardized methodology and presentations were proposed to fairly assess the economic burden of osteoporotic fracture. Results indicated substantial costs of osteoporotic fractures for pharmacy, hospitalization, emergency care, and outpatient visits in women aged ≥ 50 years in Australia, Germany, South Korea, Spain, and the USA. Purpose The objective of this multinational, retrospective matched cohort study was to use a standardized methodology across different healthcare systems to estimate the burden of osteoporotic fracture (OF) in women aged ≥ 50 years in Australia, Germany, South Korea, Spain, and the USA. Methods Within each country, healthcare resource utilization and direct costs of care were compared between patients with newly identified OF and a propensity score–matched cohort without OF during follow-up periods of up to 5 years. Results Across all five countries, the OF cohort had significantly higher rates and length of inpatient admissions compared with the non-OF cohort. In each country, the adjusted total costs of care ratio between OF and non-OF cohorts were significant. The adjusted cost ratios for pharmacy, inpatient care, emergency care, and outpatient visits were similarly higher in the OF cohort across countries. Conclusion The current study demonstrates the substantial economic burden of OF across different countries when compared with matched non-OF patients. The findings would assist stakeholders and policymakers in developing appropriate health policies.